Worldwide Phylogenetic Group Patterns of Escherichia coli from Commensal Human and Wastewater Treatment Plant Isolates - Stoppe, Nancy de Castro; Silva, Juliana S.; Carlos, Camila; Sato, Maria I. Z.; Saraiva, Antonio M.; Ottoboni, Laura M. M.; Torres, Tatiana T. (Frontiers in Microbiology, 2017)
Escherichia coli is an important microorganism in the gastrointestinal tract of warm-blooded animals. Commensal populations of E. coli consist of stable genetic isolates, which means that each host has only one phylogenetic group (PG). We evaluated the frequency of human commensal E. coli PGs from 116 people and observed that the majority of isolates belonged to group A. We also evaluated the frequency of PGs in wastewater samples and found a strong positive correlation between the PG distribution in wastewater and human hosts. In order to find out if some factors, such as geographical location and climate could influence the worldwide PG distribution, we performed a meta-analysis of 39 different studies and 24 countries, including different climates, living areas, and feeding habits. Unexpectedly, our results showed no substructuring patterns of PGs; indicating there was no correlation between PG distribution and geographic location, climate, living area, or feeding habits